2018
DOI: 10.3390/molecules23020432
|View full text |Cite
|
Sign up to set email alerts
|

The Lewis Pair Polymerization of Lactones Using Metal Halides and N-Heterocyclic Olefins: Theoretical Insights

Abstract: Lewis pair polymerization employing N-Heterocyclic olefins (NHOs) and simple metal halides as co-catalysts has emerged as a useful tool to polymerize diverse lactones. To elucidate some of the mechanistic aspects that remain unclear to date and to better understand the impact of the metal species, computational methods have been applied. Several key aspects have been considered: (1) the formation of NHO-metal halide adducts has been evaluated for eight different NHOs and three different Lewis acids, (2) the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…A better understanding of the proposed mechanism of the copolymerization of PDL and CL (Scheme ) is assumed to work via the coordination of lactones to magnesium‐center, thereby increasing the electron deficiency on the carbonyl carbon, which facilitates the ring opening through nucleophilic attack of activated alcohol, according to the previous works . The mode of alcohol activation is often described as the deprotonation/activation of an initiating alcohol species by THTP in the presence of MgI 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A better understanding of the proposed mechanism of the copolymerization of PDL and CL (Scheme ) is assumed to work via the coordination of lactones to magnesium‐center, thereby increasing the electron deficiency on the carbonyl carbon, which facilitates the ring opening through nucleophilic attack of activated alcohol, according to the previous works . The mode of alcohol activation is often described as the deprotonation/activation of an initiating alcohol species by THTP in the presence of MgI 2 .…”
Section: Resultsmentioning
confidence: 99%
“…However, only a limited number of N‐heterocyclic organic catalysts, strong acids, and phosphazene superbases are able to polymerize the PDL (Scheme ). From this perspective, cooperative catalytic systems appear attractive due to their capacity for providing a powerful alternative to enhance the polymerization activity and selectivity . Crucially, Buchmeiser, Naumann, and co‐workers reported that the inactive N‐heterocyclic carbenes in combination with Lewis acids (MgCl 2 , ZnCl 2 , SnCl 2 ) are capable of polymerizing CL.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is a typical example of aggregation-induced emission (AIE) and may be explained with that the coordination to metal ions in a complexes restricted the deformation of the ligand and the induced nonradiative relaxation. 41,42 Sensing of Cr 2 O 7…”
Section: Luminescent Propertiesmentioning
confidence: 99%
“…[16][17][18] In addition, NHOs were utilized in CO 2 functionalization, [19] transesterificiation, [20] silylation, [21] hydroborylation [22] , alkylation [23] as well as polymerization. [24][25][26][27][28] With suitable structural design, NHOs can serve as a new class of Brønsted/Lewis base organocatalysts for a wide range of chemical reactions. Up to now, all of the NHOs published were based on imidazole, [1,29] benzylimidazole, [12] triazole, [35] imidazoline [30] and six-membered enediamines [32] (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%